Biji kopi meningkatkan ekspresi glutathione padamonosit secara in vitro (Coffee beans increase glutathione expression to monocyes in vitro) - Roedy Budirahardjo (Journal of Dentomaxillofacial Science, 2015)
Some research stated that coffee may act as an antioxidant, but has not mentioned concentrations can distinguish the production of antioxidants. One of the important antioxidant roles in preventing various diseases is GSH. The researchis intended to analyze the expression of antioxidant GSH of coffee beans in vitro. Furthermore, the culture ofperipheral blood monocytes of healthy people as much as 6 cc, mixed with the anticoagulant heparin. Ficoll-Hypaquecentrifugation and suspended in RPMI 1640 medium Buffy coat separated, washed, resuspended. Cells were placedon plate 96-well microtiter of 8 x 105 cells/well, and incubated. Then added RPMI, incubated and lymphocytesdiscarded. After washing, complete medium was added and incubation. Monocytes reacted with coffee with variousconcentrations (4 groups) and incubated 18 hours. GSH then analyzed by immunocytochemistry method. GSH cellsexpressing brown and counted under a light microscope (400x). The results indicated that a concentration of 3 g coffeebrewed in 300 mL of hot water has the greatest ability to increase GSH. It was concluded that coffee can improveGSHexpression on monocytes were exposed to DMBA, and the higher the concentration of the coffee bean, the higherthe expression of GSH.